The Analysis Of Fraud Hexagon Towards Earnings Management - Deva Djohan; Duffin Duffin (Riviera Publishing, 2022)
Introduction: The COVID-19 pandemic has emerged and is still raging around the world and as can be seen from the severity of the COVID-19 pandemic, it has led to rampant fraud committed by many corporations, especially in Indonesia. According to a survey conducted by RSM Indonesia (2020), 80% of respondents stated that in the midst of the pandemic, fraud committed in Indonesia was increasing in their own organizations. Although the least common type of fraud is financial statement fraud, the losses incurred are quite large. The most cases occurred in the banking sector in 2020. The formulation of the research problem that the author wrote was to examine more deeply the impact of the hexagon fraud factor on financial statement fraud determined by discretionary accruals. Objective: This study aims to determine the effect and correlation of all hexagon fraud proxies on financial statement fraud using discretionary accruals in the banking sector listed on the Indonesia Stock Exchange (IDX) from 2018-2020. Methods: The research design is a quantitative design with descriptive and correlational methods, especially multiple linear regression analysis. Results: The findings of this study are that financial stability and the nature of the industry and rationalization have a positive and significant effect on discretionary accruals. Meanwhile, personal financial needs, financial targets, capabilities, and collusion have a negative and insignificant effect on discretionary accruals. In addition, external pressure, effective monitoring and ego/arrogance have a positive and insignificant effect on discretionary accruals. Conclusion: The conclusion of this research is as follows: 1. Stimulus as measured by financial stability, opportunity as measured by nature of industry, and rationalization as measured by total accrual to total assets ratio has significant impact towards earnings management in banking sector of Indonesia Stock Exchange.